2000
DOI: 10.1002/1529-0131(200008)43:8<1698::aid-anr5>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Soluble complement receptor 1 (CD35) delivered by retrovirally infected syngeneic cells or by naked DNA injection prevents the progression of collagen-induced arthritis

Abstract: Objective. The complement system is important in the development of autoimmune inflammation, including rheumatoid arthritis (RA) and collagen-induced arthritis (CIA). Complement receptor 1 (CR1) is involved in regulation of complement activity. Studies on models of autoimmunity have demonstrated that soluble CR1 (sCR1) is a potent therapeutic agent. The present study was thus undertaken to investigate the feasibility of antiinflammatory gene therapy to prevent CIA by delivery of genes encoding truncated sCR1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 76 publications
1
39
0
1
Order By: Relevance
“…receptor could effectively inhibit the development of arthritis, 34,35 the present study suggested that gene therapy for RA using the intramuscular gene delivery with a plasmid vector might be a therapeutically plausible form of RA treatment. This direct DNA transfer method has several advantages over viral vectors.…”
Section: Il-1ra Dna Injection Inhibits Cia J-m Kim Et Almentioning
confidence: 58%
“…receptor could effectively inhibit the development of arthritis, 34,35 the present study suggested that gene therapy for RA using the intramuscular gene delivery with a plasmid vector might be a therapeutically plausible form of RA treatment. This direct DNA transfer method has several advantages over viral vectors.…”
Section: Il-1ra Dna Injection Inhibits Cia J-m Kim Et Almentioning
confidence: 58%
“…Difference between the C3 -/-group and the FB -/-group, p X 0.005. complement activation [23,24]. We have previously shown that both of these pathways are deleterious in CIA in mice [25].…”
Section: Introductionmentioning
confidence: 98%
“…In addition we have been able to extend these observations to a therapeutic gene, sCR1 which is a potent inhibitor of the complement cascade 21 with proven effect by gene therapy in a mouse arthritis model. 22 Regulated expression of sCR1 from per-manent transfectants with the construct GTRTC displayed maximal regulation in excess of 70-fold. The improved regulation observed with permanent transfectants probably occurs via favourable interactions with DNA sequences adjacent to the site of integration which reduce basal expression and enable good induction of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…22 The sCR1 gene was removed from this vector by the restriction NcoI-blunted-NotI, and cloned into the pGT vector cut with EcoRV-NotI, forming the inducible vector pGTC1. The autoregulatory vector expressing sCR1 required transfer of the tetP-sCR1 cassette (restricted NheI-BspMI) from pGTC1 and cloned into pGTRTL cut with the same enzymes, producing the autoregulatory vector pGTRTC (Figure 1).…”
Section: Cloning Strategymentioning
confidence: 99%
See 1 more Smart Citation